Reliability Based Maintenance Strategy Selection in Process Plants: A Case Study. (2016) - Vishnu, C.R.; Regikumar, V.
Abstract: The importance of maintenance function has increased due to its role in keeping and improving the availability, product quality, safety requirements and operating cost levels of the process plants. Accordingly, maintenance strategy selection became one of the most important decision making activity in the industry. This paper proposes a general approach to implement Reliability Centered Maintenance (RCM) in process plants. RCM is a recently evolved maintenance strategy that incorporates all the advantages of traditional maintenance strategies. More precisely, RCM selects the most appropriate and tailor made maintenance strategy for all the equipment in the plant based on its criticality score and reliability parameters. RCM implementation requires the collection and analysis of historical failure and maintenance data to determine current condition of the equipments. Subsequently, maintenance strategy is framed for the unit by following Analytical Hierarchy Process (AHP) based methodology. This should be done by taking expert opinions of personals from both the maintenance and production departments. RCM implementation model presented here is validated with the maintenance history data of a process plant manufacturing titanium dioxide with a production capacity of 20, 000 metric tonnes per annum. Currently the firm follows a combination of scheduled and breakdown maintenance strategies. However, RCM implementation in this plant is justified by the maintenance simulation results that revealed the current poor availability and performance of the equipments.